Predictors of adjustment to college among Vietnamese students: A mixed methods study - Le, Phuong Thi (Animo Repository, 2019)
In order to gain more knowledge about students’ college life adjustment which has been described as one of the most changing times of one’s life, this explanatory sequential mixed methods study investigated the relationship between Needs Satisfaction, Collective Self-Esteem (CSE), Personal Self-Esteem (PSE) and adjustment to college among Vietnamese students. Specifically, this study examined the prediction of these factors to adjustment, and explained how they contributed to students’ adjustment to college. There were 505 college students who participated in the Quantitative Phase (Male = 43.2%, Female = 56.8%), with ages ranging from 18 to 25 years (M = 20.60, SD = 1.69). Multiple linear regression was used to analyze the data. Results showed that the five predictors significantly explained 49% of students’ adjustment to college. In the Qualitative Phase, thematic analysis showed that situations the participants faced allowed for the needs of autonomy, competence, and relatedness to be met in various ways, and meeting these needs facilitated adjustment. Participants also evaluated highly their social groups and showed their positive self-evaluation as crucial resources to support their adjustment to college life. Overall, findings showed that these college students in their emerging adulthood stage are striving for autonomy and competence, creating good social and personal relationships, and establishing their own identity. Therefore, students with high basic Needs Satisfaction, CSE and PSE better adjusted to college. Implications for the counseling practice, for college administrators and related agency, and for future research were discussed.